DIRECTIONS AND PROSPECTS FOR THE DEVELOPMENT OF HUMAN CAPITAL IN THE REGION - Abdikarimov Islombek Ibragimovich (American Journals, 2025)
This article is a comprehensive study of the role and importance of human capital in modern economics. The theoretical and methodological foundations of the formation and development of human capital, its role in increasing the innovative potential of the country and its transformation in the conditions of the digital economy are studied. Also, the reforms carried out in Uzbekistan on the development of human capital, the existing problems and their solutions have been analyzed. On the basis of international experience, scientifically based proposals have been developed to improve the quality of the country's human capital, effectively manage it and ensure innovative development. The article also covers the issues of the development of human capital by modernizing the educational system, improving personnel skills, strengthening the integration of Science and production.
Keywords: Human capital, intellectual potential, educational system, professional development, innovative activities, labor productivity, competitiveness, economic growth, digital transformation, intellectual property, investment efficiency, personnel potential, quality of Education.